Activist dispositions for social justice in advantaged and disadvantaged contexts of schooling. Issue 5 (4th July 2019) - Mills, Carmen; Gale, Trevor; Parker, Stephen; Smith, Catherine; Cross, Russell
Abstract: This article advances current conceptions of teacher activism through an exploration of the social justice dispositions of teachers in advantaged and disadvantaged contexts of schooling. We interrogate the practices of teachers in a government school, with a high proportion of refugee students and students from low socio-economic backgrounds, in a high-fees, multi-campus independent school, and in a disadvantaged Systemic Catholic school to illustrate how Bourdieu's notion of dispositions (which are constitutive of the habitus) and Fraser's distinction between affirmative and transformative justice are together productive of four types of teacher activism. Specifically, we show that activist dispositions can be characterised as either affirmative or transformative in stance and as either internally or externally focused in relation to the education field. We argue that the social, cultural and material conditions of schools are linked to teachers' activist dispositions and conclude with the challenge for redressing educational inequalities by fostering a transformative activism in teachers' practices.